2010
DOI: 10.1093/ndtplus/sfq069
|View full text |Cite
|
Sign up to set email alerts
|

Results of renal re-transplant in Spain (1990-2002)

Abstract: Background. Renal re-transplants are increasing in number, due to many first renal transplant patients coming back to dialysis treatment. There are controversial opinions about the evolution of these re-transplanted patients. The aim of our study is to analyse the prognosis of patients and grafts under a renal re-transplant.Methods. This was a retrospective study of 579 renal re-transplants realized in 15 Spanish different centres in the years 1990, 1994, 1998 and 2002 including all renal re-transplants realiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…22 It has also been proved that generally active CMV infection occurred in 30-70% of transplant recipients with a mortality rate of 5%. [23][24][25][26][27] Since effective anti-CMV treatment is available and the number of CMV copies well correlated with the severity of clinical symptoms, early detection of CMV DNA in the blood is of great importance in identifying those patients who are at risk of infection and disease progression. 28 Some studies reported co-infection of CMV/EBV.…”
Section: Discussionmentioning
confidence: 99%
“…22 It has also been proved that generally active CMV infection occurred in 30-70% of transplant recipients with a mortality rate of 5%. [23][24][25][26][27] Since effective anti-CMV treatment is available and the number of CMV copies well correlated with the severity of clinical symptoms, early detection of CMV DNA in the blood is of great importance in identifying those patients who are at risk of infection and disease progression. 28 Some studies reported co-infection of CMV/EBV.…”
Section: Discussionmentioning
confidence: 99%